Molluscs as crop pests - Barker, G. M. (CABI Pub., 2002)
This 19-chapter book discusses the biology (including reproduction, life history, feeding preferences and sexual behaviour) of molluscs as pests of horticultural, field and fodder crops, and outlines the development of appropriate mechanisms for the control of these pests (mainly biological, cultural and chemical). Two chapters review progress towards the development of chemical control strategies, one addressing the toxicology of chemicals, the other the deployment of molluscicides in baits. These chapters also highlight the statistical and biological procedures for screening and evaluating molluscicides which are not a component of the standard procedure of mollusc control. A series of chapters focus on specific crop situations, providing a synopsis of the current pest status of gastropod species or species groups.